Psychodrama technique in enhancing communications skills among Special Education Integration Program (SEIP) students in Malaysia: a case study - Siti Khadijah Hashim; Abu Yazid Abu Bakar (Education and Social Sciences Review, 2020)
This study aimed to determine the effectiveness of psychodrama technique in enhancing social   interaction among Special Education Integration Program (SEIP) students in Malaysia. The objectives of the     study were to train SEIP students to communicate well through psychodrama, to increase self-confidence when communicating and to expose students to self-management through  psychodrama. The study was conducted via group session on a psychoeducational program   involving 13 students with different learning disabilities at Sekolah Kebangsaan Taman Seri Mawar, Negeri Sembilan. The results show that SEIP students knew the knowledge on how to manage themselves but still need to be improved in terms of communication skills and social   interaction in groups.